2021
DOI: 10.1002/jnr.24958
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect and possible therapeutic application of xenon in neurological diseases

Abstract: Xenon is an inert gas with stable chemical properties which is used as an anesthetic.Recent in vitro and in vivo findings indicate that xenon also elicits an excellent neuroprotective effect in subanesthetic concentrations. The mechanisms underlying this primarily involve the attenuation of excitotoxicity and the inhibition of N-methyldaspartic acid (NMDA) receptors and NMDA receptor-related effects, such as antioxidative effects, reduced activation of microglia, and Ca 2+ -dependent mechanisms, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 96 publications
(123 reference statements)
0
6
0
2
Order By: Relevance
“…Additionally, previous research has demonstrated the cascade signaling of apoptosis induced by caspase-3 during oxidative stress injury ( Kim et al, 2020 ; Vega-García et al, 2021 ). Glutamate-mediated excitotoxicity could cause the excessive production of ROS and neuronal injury, triggering the caspase 3-induced apoptosis signaling pathway ( Levite, 2014 ; Zhao et al, 2021 ), even leading to cell death ( Zhang et al, 2021 ); this process is considered to be closely related to epileptic development ( Yang et al, 2016 ). According to the previous reports, xenon could attenuate glutamate accumulation ( Roostan and Frishman, 2018 ), reduce the level of oxidative stress ( Lavau et al, 2017 ), and alleviate cell apoptosis ( Gill and Pickering, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous research has demonstrated the cascade signaling of apoptosis induced by caspase-3 during oxidative stress injury ( Kim et al, 2020 ; Vega-García et al, 2021 ). Glutamate-mediated excitotoxicity could cause the excessive production of ROS and neuronal injury, triggering the caspase 3-induced apoptosis signaling pathway ( Levite, 2014 ; Zhao et al, 2021 ), even leading to cell death ( Zhang et al, 2021 ); this process is considered to be closely related to epileptic development ( Yang et al, 2016 ). According to the previous reports, xenon could attenuate glutamate accumulation ( Roostan and Frishman, 2018 ), reduce the level of oxidative stress ( Lavau et al, 2017 ), and alleviate cell apoptosis ( Gill and Pickering, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kubota et al (2020) found that xenon could significantly inhibit the glutamatergic responses in the hippocampal region of brain, reducing the uptake of glutamate. Besides, some evidence suggests that xenon inhibits transmission and uptake of glutamate as well as further inhibit NMDA receptors through binding at the interface of NR1 and NR2 subunits (Dickinson et al, 2007;Liu et al, 2010;Zhang et al, 2021). Recently, TREK-1 gene was found to be activated by xenon, which is considered to be associated with the activation of Ca 2+ channels, reduction of glutamate release and inhibition of excitotoxicity (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous review ( Zhang et al, 2021 ), xenon exerts neuroprotective effects involving not only the inhibition of N -methyl-daspartic acid (NMDA) receptors, attenuation of excitotoxicity, and NMDA receptor-related effects ( Wilhelm et al, 2002 ), such as antioxidative effects, reduced activation of microglia, and Ca 2+ -dependent mechanisms, as well as interaction with certain ion channels. Previous reports have confirmed the significant neuroprotective effects of xenon through antioxidant action ( Yang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Аргон уже используется в различных областях науки и медицины [92][93][94][95][96][97][98][99][100], в которых показана безопасность его применения, в том числе при изучении показателей гемодинамики (сердечный выброс), объема легких с помощью оценки поглощения инертного растворимого газа из легких, работе респираторного масс-спектрометра [101][102][103]. В отличие от аргона, другой благородный газ, ксенон, уже одобрен для клинического применения в качестве общего анестетика и подтвердил свои нейропротекторные свойства в многочисленных исследованиях in vitro и in vivo [104][105][106][107][108][109][110][111][112].…”
Section: кардиопротекторные свойстваunclassified